The Communication Strategy of Mangkunegara X in Promoting the Creative Economy in Solo through the Mangkunegaran Run 2025 Event - Amelia Fitriani (LSPR Institute of Communication & Business, 2026)
This study explores the communication strategy of Kanjeng Gusti Pangeran Adipati Arya (K.G.P.A.A.) Mangkunegara X in promoting the creative economy in the city of Solo through Mangkunegaran Run 2025, a cultural and sporting event designed to embody his visionary concept of Culture–Future. The research focuses on how leadership rooted in cultural heritage can employ strategic communication to foster public engagement and stimulate the growth of the local creative economy. Using a qualitative approach through a case study method, this research gathers data from direct observation, documentation, news coverage, and relevant scholarly works on cultural leadership, strategic communication, and creative economy development. The theoretical framework combines the concepts of Integrated Marketing Communication (IMC) and Cultural Branding to analyze how cultural values are translated into public narratives and experiential communication during the event. This study aims to identify the key elements of Mangkunegara X’s communication strategy in reframing a cultural event as a driver of economic innovation. It also examines how symbolic representation, narrative framing, and stakeholder engagement contribute to shaping the identity of Mangkunegaran as a dynamic and creative cultural institution. The findings are expected to provide insights into how traditional leadership can adapt to the demands of modern communication, offering implications for cultural institutions seeking to revitalize heritage through entrepreneurship. Accordingly, this research contributes to the broader discourse on creative economy strategies and deepens the understanding of communication practices within contemporary cultural governance.